Invertebrados do solo e da parte aérea nas roças de arroz (Orysa sativa): impactos do pousio melhorado com sabiá (Mimosa caesalpiniifolia) e do manejo de fogo e nutrientes - Froz, Dayane Valessa Barros (2022)
The intensification of soil use and consequent degradation in regions of northeastern Brazil has increased in the last decade, resulting in the loss of natural soil fertility. The improvement of fallow with leguminous species can contribute to the recovery of chemical and biological fertility of the soil, contributing to the conservation of its edaphic biodiversity compared to spontaneous vegetation. In this context, the objective of this work was to investigate the effects of improved fallow for 6-7 years with the native tree legume Sabiá (Mimosa caesalpiniifolia Benth.) on the abundance and diversity of soil and aerial part biota in paddy rice fields. tall. The experimental areas are located in the municipality of Pirapemas - MA, the experimental scheme was a split-plot, with the main treatment (after sabiá vs. after spontaneous capoeira), subdivided into four sub-plots (control, cutting and burning, fertilization NPK and urea fertilization) and planted with rice in the growing years of 2020 and 2021. To evaluate the mesofauna, soil collection rings were used, subsequently placed in the Berlese-Tüllgren Funnel for seven days. In the evaluation of the macrofauna, pitfall traps were used, buried at the soil surface level for 24 hours. For the evaluation of arthropods in the aerial part, rice plants were collected through direct attack and placed in paper bags. Then, all collected material was taken to the Entomology/Acarology laboratory for washing, screening and taxonomic identification. Among the analyzed vegetation, the thrush legume and spontaneous weeds in rice cultivation did not show significant effects on the abundance and diversity of biota in the soil and part of the area in rice fields. On the other hand, the edaphic mesofauna showed the greatest diversity in areas with thrush tree legume. Soil macrofauna was favored with greater diversity in spontaneous capoeira areas. The highest frequency of arthropods occurred in the taxonomic categories Collembola, Araneae and Coleoptera in the different treatments and sub-treatments. Based on the analysis of diversity, abundance and relative frequency, it can be concluded that arthropods are affected by different conditions of soil use and management.